ANALISIS PERSEDIAAN BAHAN BAKU DAN USAHA INDUSTRI KERUPUK KULIT (Studi Kasus Home Industry “Kerupuk Jangek Asli Khas Malalo”) DI KOTA LUBUKLINGGAU PROVINSI SUMATERA SELATAN - Novi Cahyani; Irnad Irnad; Reswita Reswita (Sekolah Tinggi Pariwisata Mataram, 2021)
The research aimed are to: 1) Show the most economical amount of raw material orders, safety stock, and re-ordering points, 2) Calculated profits, 3) Account to the break-even point of production and, 4) Evaluated business capability in gaining profits of the “Kerupuk Jangek Asli Khas Malalo” industry in Lubuklinggau in Sumatra Province South. The method of data analysis in this study used quantitative and qualitative analysis. The results of this study indicated that the most economical amount of raw material orders was 1.692 kg / month, safety inventory was 233kg / month, reorder point was 390kg / month, net income of operation in industry was earned Rp.28.588.309 and total net income of sale was Rp.55.588.309, break-even point in the industry “Kerupuk Jangek Asli Khas Malalo” was Rp. 7.391.761 or 57.84 kg, and for the analysis of profitability in the industry “Kerupuk Jangek Asli Khas Malalo” that was equal to 38% of total sales.